A new process for customized patient-specific aortic stent graft using 3D printing technique. (March 2020) - Lei, Yang; Chen, Xin; Li, Zhen; Zhang, Lei; Sun, Wei; Li, Lei; Tang, Feng
Highlights: A new fabrication method for personalized stent graft based on 3D printing technology is proposed. The stent graft is made up of PU film and nitinol stent. Stent performance matches the invasive surgery requirements. The fabrication of a personalized stent graft can be achieved in 3-4 days. Abstract: Endovascular aneurysm repair (EVAR) is a popular and effective treatment for descending aortic disease. However, the majority of existing coating stents used in EVAR are of a standard design which may not meet the size or structural requirements of different patients. Therefore, in this paper, we propose using 3D printing and controlled deposition as a patient-specific aortic stent graft manufacturing technique. The methodology involves the use of a rapid prototyping study sacrificial core-coating forming (RPSC-CF) technique to develop an aortic stent graft that consists of a film and metallic stent. Polyether polyurethane and nickel-titanium alloys were chosen due to their shape memory properties and good biocompatibility. The resulting customized stent grafts meet the demands of personalized therapy and invasive surgery, and perform well as demonstrated from burst pressure testing and the degree of radial support provided and radial support force tests, laying the foundation for precise aortic dissection treatment.